IL-6 is Upregulated in Late-Stage Disease in Monkeys Experimentally Infected with Trypanosoma brucei rhodesiense - Dawn Nyawira Maranga; John Maina Kagira; Christopher Kariuki Kinyanjui; Simon Muturi Karanja; Naomi Wangari Maina; Maina Ngotho (Clinical and Developmental Immunology)
The management of human African trypanosomiasis (HAT) is constrained by lack of simple-to-use diagnostic, staging, and treatment tools. The search for novel biomarkers is, therefore, essential in the fight against HAT. The current study aimed at investigating the potential of IL-6 as an adjunct parameter for HAT stage determination in vervet monkey model. Four adult vervet monkeys (Chlorocebus aethiops) were experimentally infected with Trypanosoma brucei rhodesiense and treated subcuratively at 28 days after infection (dpi) to induce late stage disease. Three noninfected monkeys formed the control group. Cerebrospinal fluid (CSF) and blood samples were obtained at weekly intervals and assessed for various biological parameters. A typical HAT-like infection was observed. The late stage was characterized by significant (P<0.05) elevation of CSF IL-6, white blood cell count, and total protein starting 35 dpi with peak levels of these parameters coinciding with relapse parasitaemia. Brain immunohistochemical staining revealed an increase in brain glial fibrillary acidic protein expression indicative of reactive astrogliosis in infected animals which were euthanized in late-stage disease. The elevation of IL-6 in CSF which accompanied other HAT biomarkers indicates onset of parasite neuroinvasion and show potential for use as an adjunct late-stage disease biomarker in the Rhodesian sleeping sickness.